The lytic polysaccharide monooxygenase CbpD promotes Pseudomonas aeruginosa virulence in systemic infection - Fatemeh Askarian (Nature Portfolio, 2021)
The Pseudomonas aeruginosa lytic polysaccharide monooxygenase CbpD, prevalent in clinical isolates, has been proposed to act as a virulence factor. Here, the authors combine structural work, in silico simulations, enzymatic activity and in vitro and in vivo experiments to further delineate the role of CbpD and show that its deletion renders P. aeruginosa unable to establish a lethal systemic infection, leading to enhanced bacterial clearance in a mouse model of infection.